Theoretical and experimental study on cutting temperature in the presence of drilling fluid during ice-core drilling - Zhuo Chen; Pinlu Cao; Han Wang; He Yang; Qilei Yin (Journal of Glaciology)
Warm ice at temperatures close to the pressure melting point is often encountered in deep ice-core drilling. The heat generated by rotary cutting can melt ice chips, which seriously threatens the safety of drilling if the chips refreeze on the drill bit or barrel. Lowering the cutting heat is an effective method to reduce the melting of ice chips. In this study, a general theoretical model was established based on heat transfer theory and the cutting mechanism to calculate and analyze the cutter temperature during the circulation of the drilling fluid. The model was validated by a series of experiments, which demonstrated reasonable agreement between the calculated data and experimental results, with a maximum error of <16%. The factors that contribute to the rise in the cutter temperature during warm ice drilling were investigated. Results suggest that the drilling fluid has excellent cooling performance, and its type and flow rate have minimal impact on the cutter temperature. To mitigate the cutter temperature rise, maximizing the rake angle and thermal conductivity of the cutter, while minimizing the rotation speed of the drill bit, cutting depth, cutter width and friction coefficient between the ice and cutter is recommended.